EVALUASI EFISIENSI PENGELOLAAN PERBEKALAN FARMASI DAN PENGENDALIAN OBAT EXPIRED DATE DI INSTALASI FARMASI RSUP FATMAWATI - Muni Fathuzzahra Muni (RSUP Fatmawati, 2026)
Background: Efficient pharmaceutical supply management is a crucial aspect of hospital operations to ensure medicine availability and prevent financial losses due to expired drugs. Objective: This study aims to evaluate the efficiency of pharmaceutical supply management and the control system for expired medicines at the Pharmacy Installation of RSUP Fatmawati. Methods: The evaluation was conducted by analyzing management components from planning, procurement, and storage to distribution, as well as identifying factors causing drug expiration through observation and secondary data review. Results: Management at RSUP Fatmawati followed standard operating procedures; however, challenges in planning accuracy and stock monitoring systems were still identified. Control of expired medicines is implemented through the First Expired First Out (FEFO) system and an Early Warning System (EWS) involving special labeling 3–6 months prior to expiration. Conclusion: Management efficiency can be improved by optimizing the pharmacy management information system and strengthening supervision in storage areas to minimize dead stock and losses due to expired medicines. Keywords: Efficiency, Pharmaceutical Management, Expired Medicine, RSUP Fatmawati.